Cross Country Evidence on the Cointegration and Causality Relationships Between Economic Growth and CO2 Emissions in OECD Countries - Marceda Bach, Tatiana; Tortato, Ubiratã; Vieira da Silva, Wesley (International Journal of Industrial Engineering and Management, 2018)
This article aims to verify the existence of a relationship of cointegration and causality between economic growth and CO2 emissions in 22 member countries of the OECD, in a time series from 1961 to 2011. The results indicate thateconomic growth and CO2 are in balance in the long run for ten countries. The causality test showed a bilateral relationship, suggesting that variations in economic growth cause CO2 emissions and CO2 emissions cause economic growth. Long and short-term alternative measure, such as reforestation, the fight against deforestation, the use of wind, nuclear, and solar power, electric vehicles, incentives for the use of public transport, capture and storage of CO2 are recommended for countries that CO2 caused economic growth. Thus, it is concluded that there is evidence of long-term and causal relationships between economic growth and CO2 emissions. Article history: Received (06.09.2017); Revised (08.11.2017); Accepted (10.01.2018)